SELF-ACTUALIZATION OF VIOLA HASTING IN SHE'S THE MAN MOVIE 2006) DIRECTED BY ANDY FICKMAN: A HUMANISTIC PSYCHOLOGICAL APPROACH - ARISTA , EREKA NOOR (2011)
The major problem of this study is self-actualization especially reflected in Andy Fickman's She's the Man (2006) movie. The purpose of the research is to analyze the movie based on the structural elements and to analyze the movie based on the humanistic psychological perspective. The type of the research is qualitative. The primary data source that is used by the writer is She's the Man movie and this script which is written by Brian bird. Movie script was taken from a website. The secondary data are taken from the other sources which relate to this movie such as biography of the author and the other relevant information. The method of collecting data is library research whereas the technique for analyzing is descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis, it is indicated that each of narrative and technical element is interrelated to each other. Secondly, based on the humanistic psychological, it depicts the struggle of a girl who has a big dream to be a soccer player. The major character is a characterization of the human who wants to get her desire although she must break the rules and lies to everyone about her identity. Self-actualization is prominent thing in this story.